The tourism supply chain management: Case Study on Mount Kelud, Kediri regency - Romy Hermawan; Edriana Pangestuti; Gigih Artono; Supriono Supriono (International Journal of Green Tourism Research and Applications, 2023)
Tourism is a lucrative sector for a country looking to boost its economy. The tourism industry can generate state income in the form of foreign exchange, therefore this tourism industry must be considered if a country wants its economy to rise. One way that can be done to increase the competitiveness of the tourism industry is to carry out comprehensive supply chain management. In this study the type of descriptive research selected and its approach with a qualitative research approach. So that the research location and research site is the Mount Kelud Tourism Area, Kediri Regency. Through the results of interviews, observations, and surveys related to the focus of research to related parties, there were 5 informants as primary data sources which were determined by researchers with certain considerations, namely the Tourism and Culture Office of Kediri Regency, tourism managers, visitors, motorcycle taxi associations, and traders associations. The results show that Mount Kelud tourism has very good potential to be developed. The lack of coordination between the two parties, namely between the government and the manager to improve existing facilities, becomes a problem such as adding photo spots which are considered insufficient and also expanding the parking area which is a problem because it is considered not spacious enough to accommodate many vehicles when the holidays arrive. The products sold are also less varied, namely only pineapple products and their derivatives such as pineapple chips, pineapple juice, pineapple candy, and others. So that visitors are not satisfied with the products sold because the products are less varied.